Target Therapies in Pancreatic Carcinoma - Silvestris, Nicola; Gnoni, Antonio; Elisabetta Brunetti, Anna; Vincenti, Leonardo; Santini, Daniele; Tonini, Giuseppe; Merchionne, Francesca; Maiello, Evaristo; Lorusso, Vito; Nardulli, Patrizia; Azzariti, Amalia; Reni, Michele (Current Medicinal Chemistry, 2014)
Pancreatic ductal adenocarcinoma (PDAC) occurs in the majority of cases with early locoregional spread and distant metastases at diagnosis, leading to dismal prognosis and limited treatment options. Traditional cytotoxic chemotherapy provides only modest benefit to patients with PDAC. Identification of different molecular pathways, overexpressed in pancreatic cancer cells, has provided the opportunity to develop targeted therapies (monoclonal antibodies and small-molecule inhibitors) and peculiar new class of taxanes with a crucial therapeutic role in this cancer setting. A phase III trial has shown that erlotinib in combination with gemcitabine was clinically irrelevant and skin toxicity can be a positive prognostic factor. Moreover, the combination of cetuximab or erlotinib with radiotherapy in advanced pancreatic cancer has shown to be synergistic and a reversal of radio-resistance has been suggested by inhibition of VEGF/EGFR pathway. To overcome EGFR-inhibition therapy resistance several alternative pathways targets are under investigation (IGF- 1R, MMPs, Hedgehog proteins, m-TOR, MEK, COX-2) and provide the rationale for clinical use in phase II/III studies. Also nab-paclitaxel, a new taxanes class, uses high pancreatic albumin-binding protein SPARC levels to act in cancer cells with a less toxic and more effective dose with respect to classic taxanes. Understanding of molecular pathogenesis of pancreatic adenocarcinoma continues to expand. However, many promising data in preclinic and phase I/II trials did not yield promise in phase III trials, suggesting that identification of predictive biomarkers for these new agents is mandatory. The knowledge of biologic and molecular aspects of pancreatic cancer can be the basis for future therapeutic developments.
Keywords: vascular endothelial growth factor (VEGF)